FLUKTUASI SUHU UDARA PADA EKOSISTEM HUTAN KOTA - Nonong Krisnawati Loha; Johan A. Rombang; Josephus I. Kalangi (Universitas Sam Ratulangi, 2022)
Abstract This study aims to determine fluctuations in air temperature in urban forest ecosystems. This research was carried out in 3 (three) places, namely Tomohon urban forest (921 meter above sea level), Bitung urban forest (Danowudu 248 meter above sea level) North Minahasa urban forest (Kenangan 342 meter above sea level), conducted in November 2021, for 5 days. Observation plots measuring 25x25 m at each location. The diameter of the crown was measured using the